Protocol of early physiotherapeutic intervention in patients with acute stroke intra-hospital: systematic review - Junior, Paulo Roberto Fonseca; Vale, Vanessa Donato do (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: Stroke is associated with high rates of mortality and disability. Physiotherapy plays a key role in the treatment these patients. Early rehabilitation proves to be an important point in the recovery process, as it helps to reduce complications and loss of functional capacity. Objective: This systematic review aims to analyze the effects of early physiotherapy protocols on recovery after acute stroke intra-hospital. Methods: The research sought references with publication date between January 2010 and March 2017, through a database such as MedLine (by PubMed), Lilacs, Cochrane Library, Scielo and PEDro. Results: A total of 30 articles were identified. After reading their titles, abstracts and full texts, and being evaluated, punctuated and qualified by the PEDro and Jadad scale, only 6 articles were selected for this review. Conclusion: This study provides an insight into the variety of approaches adopted by therapists that can be used in this type of population, demonstrating improvement in several motor and functional aspects, and confirming that the intervention performed at an early stage is safe and without contra- indications.